Using multi-criteria decision methods for selecting a language school - Mileine Henriques Elias Velasco; André Luís Policani Freitas (Revista Produção Online, 2014)
Nowadays, the interest of organizations by professionals who have deep knowledge concerning more than one language has been increasing. In this scenario, the choice of a language school has been one of the most common decision problems, which has been often made on the basis of word-of-mouth, marketing activities of schools and trials without criteria. In order to contribute to this problem, this paper presents a study in which two multi-criteria decision aid methods (AHP and Weighted Average) were used to select a language school. Thus, the degree of importance of criteria relating to the problem and the degree of satisfaction of undergraduate and postgraduate students in relation to language schools they study were taken into account. The best ranked language school was the same for both MCDA methods, although some schools have obtained different positions. It was found that the analysis with AHP is richer and more elaborate than with the Weighted Average method. However, the large number of pairwise comparisons which were required to the study demanded significant attention and cognitive effort from the decision maker, and more time to perform the analysis - aspects that may contribute to the preference for the Weighted Average method in similar studies.